ความแปรปรวนของจำนวนเชื้อราในอากาศกับการระบายอากาศและสภาวะอากาศภายในห้องของโรงพยาบาลกลาง - กุลธิดา เลิศเชาวยุทธ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This study carried out measurement of temperature, relative humidity, wind velocity and ventilation rate together with concentrations of particulate matter and airborne fungi and Aspergillus sp. in Klang hospital with split type air conditioning, central air conditioning and natural ventilation system. Airborne fungi and Aspergillus sp. were sampled by Single Stage Bio-Impactors. Nutrient used for cultivating airborne fungi and Aspergillus sp. were Malt Extract Agar (MEA). At the time of sampling, PM10, PM2.5, activities and density of people in the room were recorded. The results showed that natural ventilated rooms had the highest temperature, relative humidity, wind velocity and air change rate. The PM10 and PM2.5 concentrations in natural ventilated rooms were higher than mechanical ventilated rooms (split type air conditioning and central air conditioning system) (p = 0.019 and p = 0.021) as well as airborne fungi and Aspergillus sp. were higher in natural ventilated rooms (p = 0.000 and p = 0.000). In regards to ventilation system and activities, it was found that PM10 and PM 2.5 were highest in in-patient wards with natural ventilation. Airborne fungi and Aspergillus sp. were also highest in in-patient wards with natural ventilation. The study found no relationship between airborne fungi and Aspergillus sp. with temperature, relative humidity, wind velocity, density of people, PM 2.5 and PM10.